2018
DOI: 10.1039/c8ra05825c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of an efficient and stable Al/Fe pillared clay catalyst for the catalytic wet air oxidation of phenol

Abstract: A facile method for synthesizing Al/Fe pillared clays (PILCs) from natural bentonite clay, by using ultrasonic treatment during the aging and intercalation steps, has been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 51 publications
3
11
0
Order By: Relevance
“…A characteristic that is determinant for the use of an LDH is its profile of evolution of phases by thermal treatment, which allows dehydration, deanionization, and dehydroxylation, with the subsequent formation of a variety of double and simple mixed metal oxides [8][9][10] Among the main applications that have been found to thermally decompose the products of LDHs is heterogeneous catalysis [11][12][13][14]. More specifically, heterogeneous catalysis assisted by irradiation of ultraviolet and visible light as an advanced process of oxidation of recalcitrant and/or persistent organic molecules has become of interest as a potential application of LDHs [15,16]. Several advanced oxidation processes, such as O 3 /Ultraviolet (UV), O 3 /H 2 O 2 , UV/H 2 O 2 , Fenton, UV/Fenton, and UV/TiO 2 , have been applied in wastewater as a treatment to mineralize many organic chemicals [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…A characteristic that is determinant for the use of an LDH is its profile of evolution of phases by thermal treatment, which allows dehydration, deanionization, and dehydroxylation, with the subsequent formation of a variety of double and simple mixed metal oxides [8][9][10] Among the main applications that have been found to thermally decompose the products of LDHs is heterogeneous catalysis [11][12][13][14]. More specifically, heterogeneous catalysis assisted by irradiation of ultraviolet and visible light as an advanced process of oxidation of recalcitrant and/or persistent organic molecules has become of interest as a potential application of LDHs [15,16]. Several advanced oxidation processes, such as O 3 /Ultraviolet (UV), O 3 /H 2 O 2 , UV/H 2 O 2 , Fenton, UV/Fenton, and UV/TiO 2 , have been applied in wastewater as a treatment to mineralize many organic chemicals [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…F. T Zompantzi et al [21] reported 95% phenol degradation using ZnAl metal oxides. Highly stable Al/Fe pillared clay catalyst was synthesized and showed efficient remediation of phenol and total organic carbon (TOC ) from aqueous solutions [22]. MgAl precursor prepared by simple dry milling of Mg and Al salts exhibited a high sorption capacity of 82.5 and 356.4 mg/g for phenol and p-nitrophenol, indicating excellent adsorbent for the treatment of phenolic compounds from the aqueous phase.…”
mentioning
confidence: 99%
“…Deposition of pillars permanently opens the interlayer spaces of clays, therefore resulting in porous materials with a relatively high specific surface area. Considering that clay minerals modified in this way are still characterized by ion exchange properties and surface acidity, it is not surprising that they are very interesting materials [3,4].…”
Section: Introductionmentioning
confidence: 99%